Poder, política e diálogo em Hannah Arendt: compreensão e dialética - Pinto Coelho, Cláudio Novaes (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The main purpose of this paper is to reflect upon the political aspect of the epistemology of comprehension through an attempt to understand how Hannah Arendt’s thought deals with power, politics and dialogue. We present a comparative analysis of Arendt’s work and the thought of other authors who are bound to the dialectic method such as Adorno/Horkheimer and Debord. In the case of Adorno and Horkheimer, the main point of comparison is the notion of a totally administered society. Regarding Debord, the main point of comparison is the notion of spectacular power.